Coming to: consciousness and natality in early modern England - Harrison, Timothy M. (The University of Chicago Press, 2020)
Introduction : Beginnings -- Milton and the birth of consciousness. Unexperienced thought ; Human nature experienced -- Traherne and the consciousness of birth. From creation to birth ; In utero -- Locke and the life of consciousness -- Natality and empiricism.